Knowledge Resources Informing Lighting Design Practice in Egyptian TV and Film Industry - Mustafa Yousry Matbouly (ITB Journal Publisher, LPPM ITB, 2020)
This study investigated the knowledge resources informing television and film lighting design practice in Egypt and the value of suggesting scientific recommendations to be followed. A questionnaire was circulated among a considerable number of professional lighting designers, lighting directors, directors of photography and cameramen working in the Egyptian media industry. Most of those addressed by the survey indicated that their main knowledge resource during their work is likely to be their own past experience. Very few of them depend on the recommendations of scientific research. Moreover, critical analysis of the collected data showed that there is limited academic research in the discipline of lighting design available for Egyptian television and film practitioners to benefit from. It was concluded that the discipline of lighting design needs more scientific research to establish a database of findings, theories and paradigms just as any other design discipline.